O-016 In Situ Tissue Engineering: Endothelial Growth Patterns as a Function of Flow Diverter Design. (29th July 2016) - Marosfoi, M; Langan, E; Strittmatter, L; Marel, K van der; Arends, J; Loganathan, S; Hendricks, G; Puri, A; Wakhloo, A; Gounis, M
Abstract : Purpose: To identify progenitor cells involved in flow diverter (FD) endothelialization and to assess the impact of FD design on aneurysm occlusion and endothelialization patterns. Materials and methods: Sixteen complex, elastase induced aneurysms in white New Zealand rabbits were randomly treated with 2 different types of single-layer braided flow diverters made of cobalt-chrome alloys: Device-1 – 48 wires having 33 μm diameter and 145° braid angle and Device-2 – 72 wires having 32 μm diameter with a 115° braid angle. Each device had interwoven platinum wires for radio-opacity. The aneurysm occlusion rate was assessed during final DSA at 10, 20, 30 and 60 day (n = 2 per device per timepoint) using a 0–4 score scale. 1 Implanted vessels were analyzed with scanning electron microscopy (SEM) for tissue coverage and endothelialization (scored: 0–5 from no endothelial cells present, 0, to completely mature endothelial layer, 5) and immunogold labeling technique identifying CD 34+ progenitor cells. Results: Baseline characteristics (e.g., aneurysm size, neck size, PRU, parent vessel diameter) were not different between the two groups (p > 0.1). CD34 + endothelial progenitor cells (EPCs) were present on both devices (Figure 1 ) at the center of aneurysm neck and along the entirety of the devices at all timepoints. There was no significant difference in complete aneurysm occlusion rates between the devices; however, complete or near complete occlusion was more frequently observed in aneurysms with neck ≤ 4.2 mm (p = 0.008). The total tissue coverage over the surface of device-1 and device-2 was 72 ± 17.4% and 76.9 ± 13.5%, respectively (p > 0.05). The endothelial cell growth over the surface was time dependent for device-2 (Spearman's rho = 0.86, p = 0.013), but not device-1 (Spearman's rho = 0.59, p = 0.094). Endothelialization score was marginally correlated with the distance from the aneurysm neck for device-1 (Spearman's rho = 1, p = 0.083), but not for device-2 (Spearman's rho = 0.8, p = 0.33). Conclusion: Our study supports the hypothesis that the bone marrow derived CD34+ progenitor cells contribute to flow diverter endothelialization and EPCs are present throughout the healing process up to 60 days. Although there was no difference in complete aneurysm occlusion, we have preliminary evidence of temporal and spatial dependence of endothelialization on FD design. Future FD designs can incorporate these analyzes during development to accelerate in situ tissue response to the scaffold. Reference: 1 Darsaut TE, et al . AJNR Am J Neuroradiol 2012;33 :2004–2009. Disclosures: M. Marosfoi: None. E. Langan: None. L. Strittmatter: None. K. van der Marel: None. J. Arends: 5; C; Stryker Neurovascular. S. Loganathan: 5; C; Stryker Neurovascular. G. Hendricks: None. A. Puri: 1; C; Stryker Neurovascular, Medtronic Neurovascular. 2; C; Codman Neurovascular, Medtronic Neurovascular, Stryker Neurovascular. A. Wakhloo: 2; C; Stryker Neurovascular. M. Gounis: 1; C; Stryker Neurovascular, Medtronic Neurovascular. 2; C; Stryker Neurovascular, Codman Neurovascular.